1982
DOI: 10.1148/radiology.143.1.7063725
|View full text |Cite
|
Sign up to set email alerts
|

Cranial anatomy and detection of ischemic stroke in the cat by nuclear magnetic resonance imaging.

Abstract: Proton nuclear magnetic resonance (NMR) images of cat heads were obtained using a small, experimental imaging system. As a prelude to the study of experimental ischemic brain infarction, the normal cat head was imaged for identification of anatomical features. Images of one cat which had undergone ligation of the middle cerebral artery three weeks previously showed brain changes associated with chronic ischemic stroke and compared favorably with findings on computed tomography (CT). The NMR images have millime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Proton density, T 1 -weighted (T 1 W), and T 2 -weighted (T 2 W) MRI are considered as conventional MRI methods in the assessment of neurologic disorders. During the starting years of biomedical applications of MRI, these techniques demonstrated their potential to detect cerebral lesions in animal models of stroke (Buonanno et al, 1982), traumatic brain injury (Bederson et al, 1986), brain tumors (Bederson et al, 1986), and multiple sclerosis (Stewart et al, 1985). An increase in proton density, as well as T 1 and T 2 , in pathologic tissue is attributed to an increase in interstitial water associated with the development of vasogenic edema (see van Bruggen et al, 1994 and references therein) ( Fig.…”
Section: Proton Density and T 1 -And T 2 -Weighted Magnetic Resonancementioning
confidence: 99%
“…Proton density, T 1 -weighted (T 1 W), and T 2 -weighted (T 2 W) MRI are considered as conventional MRI methods in the assessment of neurologic disorders. During the starting years of biomedical applications of MRI, these techniques demonstrated their potential to detect cerebral lesions in animal models of stroke (Buonanno et al, 1982), traumatic brain injury (Bederson et al, 1986), brain tumors (Bederson et al, 1986), and multiple sclerosis (Stewart et al, 1985). An increase in proton density, as well as T 1 and T 2 , in pathologic tissue is attributed to an increase in interstitial water associated with the development of vasogenic edema (see van Bruggen et al, 1994 and references therein) ( Fig.…”
Section: Proton Density and T 1 -And T 2 -Weighted Magnetic Resonancementioning
confidence: 99%
“…The reduction in the water diffusion coefficient is now widely used in delineation of ischemic tissue by MRI, yet the biophysical mechanisms underlying the diffusion change are only partially understood. Several reports have shown that magnetic resonance (MR) contrast from prolongation of either T 1 or T 2 relaxation of tissue water protons develops only after several hours of ischemia and is an index of irreversible water accumulation (Buonanno et al, 1982; Kato et al, 1985; Knight et al, 1994). Based on the known temporal patterns, diffusion and T 2 MRI have been exploited for monitoring the evolution of ischemic tissue damage (Welch et al, 1995).…”
mentioning
confidence: 99%
“…Such time resolution would allow correlations between lactate production and clearance in vivo with other variables that can be measured noninvasively. These include intracellular pH and the state of phosphate energy stores obtained from 31P NMR experiments (6,25), the functional state of the brain as reflected in the electroencephalogram, and possibly cerebral blood flow (26). These prospects are particularly interesting in light of the probable role of high lactate concen- (Spectrum E) After 41 min at 25% 02.…”
mentioning
confidence: 99%